THE EVOLUTION OF CRIMINAL POLICE IN THE CONTEXT OF PUBLIC SECURITY IN BRAZIL (International Seven Journal of Multidisciplinary, 2025)
This article analyzes the evolution of the Correctional Police (Polícia Penal) in Brazil, emphasizing its historical transformation, constitutional recognition, and strategic role in public security. After Constitutional Amendment No. 104/2019 officially established the federal, state, and district Correctional Police, the career underwent significant structural changes, shifting from na administrative activity to na essential police institution. The study examines the trajectory from traditional prison guards and penitentiary agents to the modern correctional police officer, who is trained to confront organized crime, manage risks, and cooperate with other security forces. The conclusion indicates that the evolution of the Polícia Penal is a fundamental institutional advancement for strengthening the prison system and enhancing public safety.